Effectiveness of mucoactives (carbocisteine and hypertonic saline) in addition to usual airway clearance management with usual airway clearance management alone in acute respiratory failure (MARCH): study protocol for a multi-centre 2x2 factorial, randomised, controlled, open-label, Phase 3, pragmatic, clinical and cost-effectiveness trial with internal pilot [version 1; peer review: 2 approved] - Mike Clarke; Marc Chikhani; Cliona McDowell; Ranjit Lall; Michael McKelvey; Margaret McFarland; Brenda O'Neill; Cecilia O'Kane; Murali Shyamsundar; Gavin Perkins; Clifford C Taggart; Gordon Sturmey; et al. (NIHR Open Research)
Background Usual airway clearance management in critically ill patients with acute respiratory failure includes suctioning, humidification, use of isotonic saline, and respiratory physiotherapy techniques. Escalation to use of mucoactives occurs when secretions are difficult to clear. Use of mucoactives in clinical practice for this patient population is extensive, yet empirical and variable. Carbocisteine and hypertonic saline are the most used agents, but evidence for their effectiveness is absent or minimal. The lack of existing large-scale randomised trials comparing mucoactives to usual airway clearance management alone in critically ill patients with acute respiratory failure highlights the urgency and necessity of this study. Aim To determine whether the use of mucoactives in critically ill patients with acute respiratory failure improves clinical outcomes and is cost effective, compared to usual airway clearance management alone. Methods A UK multi-centre, 2x2 factorial, randomised, controlled, open-label, Phase 3, pragmatic, clinical and cost effectiveness trial with internal pilot. The target sample is 1956 critically ill adults. Participants will be equally allocated across four trial arms. All participants will receive usual airway clearance management. In three intervention groups, participants will receive either carbocisteine, hypertonic saline, or a combination of carbocisteine and hypertonic saline. In the fourth comparator group, participants will receive usual airway clearance management alone. The primary outcome is the duration of mechanical ventilation with secondary clinical, safety, and health resource utilisation outcomes. The trial will be reported in accordance with CONSORT guidelines. Ethical approval was granted by Leeds East (Yorkshire & The Humber) Research Ethics Committee (reference 21/YH/0234) on 28th October 2021. All participants will provide written, informed consent via either Personal or Professional Legal Representatives, and subsequently directly once capacity is regained. Trial registration Main trial: ISRCTN17683568, https://www.isrctn.com/ISRCTN17683568, 25th November 2021 Study Within A Trial: ISRCTN16675252, https://www.isrctn.com/ISRCTN16675252, 3rd November 2021 EudraCT Number, 2021-003763-94